OptiRoute: Operational Routing Algorithm for Swarm Robots - Okutan, Hüseyin Enes; Baykara, Muhammet (Institute of Electrical and Electronics Engineers Inc., 2024)
Swarm Robotics is a dynamic system consisting of robots inspired by nature and working together. Studies in this field focus on understanding how decision-making processes and communication can be carried out effectively by examining collective behaviors and coordination. In this study, an important study topic in the field of swarm robotics, which involves assigning each robot to specific targets and navigating on these targets in a way that will determine the minimum cost paths, and which has NP-Hard Combinatorics characteristics, is addressed. In order to solve this problem addressed in the study, a heuristic routing algorithm is proposed in which swarm robots can navigate by following minimum cost paths in a coordinated and collective manner. The OptiRoute algorithm, which is based on the neighborhoods of targets in a certain region and the idea that each target has information about its closest neighbor, has been tested in simulation environments based on various levels of complexity. In this context, it is observed that the proposed OptiRoute algorithm performs routing in a way that will select the minimum cost paths when the algorithm is configured to work with an appropriate number of robots according to the number of targets and characteristics of the environment. © 2024 IEEE.
OptiRoute: Sürü Robotları için Operasyonel Rotalama Algoritması
2024 Innovations in Intelligent Systems and Applications Conference, ASYU 2024 -- 16 October 2024 through 18 October 2024 -- Ankara -- 204562
Keywords: path planning; swarm intelligence; swarm robotics